2015
DOI: 10.3389/fncel.2015.00432
|View full text |Cite|
|
Sign up to set email alerts
|

Non-linear leak currents affect mammalian neuron physiology

Abstract: In their seminal works on squid giant axons, Hodgkin, and Huxley approximated the membrane leak current as Ohmic, i.e., linear, since in their preparation, sub-threshold current rectification due to the influence of ionic concentration is negligible. Most studies on mammalian neurons have made the same, largely untested, assumption. Here we show that the membrane time constant and input resistance of mammalian neurons (when other major voltage-sensitive and ligand-gated ionic currents are discounted) varies no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Through frequency mixing, the integration of two oscillations by a target that activates with a nonlinear dependence on its inputs results in the emergence of novel frequency components (Fessenden, 1902;Poole, 2015). Consistent with the fact that neurons are nonlinear integrators (Hille, 2001;Huang et al, 2015;Segev and London, 2000), it was demonstrated experimentally that frequency mixing is applicable to brain oscillations (Ahrens et al, 2002;Grossman et al, 2017). However, these experimental studies induced mixing by applying stimuli at known frequencies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Through frequency mixing, the integration of two oscillations by a target that activates with a nonlinear dependence on its inputs results in the emergence of novel frequency components (Fessenden, 1902;Poole, 2015). Consistent with the fact that neurons are nonlinear integrators (Hille, 2001;Huang et al, 2015;Segev and London, 2000), it was demonstrated experimentally that frequency mixing is applicable to brain oscillations (Ahrens et al, 2002;Grossman et al, 2017). However, these experimental studies induced mixing by applying stimuli at known frequencies.…”
Section: Discussionmentioning
confidence: 84%
“…As oscillatory signals converge and diverge within and between neuronal networks, they undergo multiple nonlinear transformations (Hille, 2001;Huang et al, 2015;Segev and London, 2000). In other fields such as electronics and acoustics, it has long been appreciated that applying a nonlinearity to the sum of two oscillations, S 1 and S 2 , with frequencies f 1 and f 2 , results in new oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that modeling leak currents exactly (i.e. non-linearly) may affect the output of neurons ( Huang et al, 2015 ).…”
Section: T2n Tutorialsmentioning
confidence: 99%
“…8, 9). While our decision to treat E L as a constant allowed us to compare our model directly to earlier ones where leak strength was used to explore model behavior, E L may in reality be nonlinearly modulated by ion dynamics (Koizumi and Smith, 2008;Huang et al, 2015). The robustness of bursting that we found with respect to variations in g L supports the claim that the ramping dynamics that we have studied will persist with the inclusion of E L dependence on dynamic ion concentrations, but incorporating this effect in the model and tuning it appropriately is beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%